Pengaruh Pembelajaran Pendidikan Matematika Realistik Indonesia (PMRI) Terhadap Kemampuan Numerasi Dan Minat Belajar - Wijayanti, Amelia Anggun; Maerhaeni, Nafida Hetty; Hastuti, Sri (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to determine the effect of the application of the Indonesian Realistic Mathematics Education (PMRI) learning model in improving students' numeracy skills and learning interests. This type of research is experimental research using pseudo-experimental or quasi-experimental designs. This research scheme uses Nonequivalent Control Group Design, where the selected control and experimental classes are given tests at the beginning of the research (pretest) and given questionnaires of interest in learning mathematics, then giving different treatment between the control class and experimental classes, then ending with final test activities (posttest) and filling out questionnaires of interest in learning mathematics. Data collection techniques use the distribution of pretest and posttest questions and questionnaires of interest in learning mathematics. The data analysis used is normality test, homogeneity test, and independent sample t-test. This research was conducted at SMA Negeri 4 Yogyakarta by involving class X E5 students as an experimental class and class X E6 students as a control class. The results showed that the Indonesian Realistic Mathematics Education (PMRI) learning model was more influential in improving numeracy skills and interest in learning mathematics for grade X students of SMA Negeri 4 Yogyakarta in the 2023/2024 academic year when compared to conventional learning models.